Pengaruh Beban Kerja Dan Stres Kerja Terhadap Produktivitas Kerja Dengan Motivasi Kerja Sebagai Variabel Intervening Pada Karyawan PT. ABC - Ismartaya Ismartaya; Erni Yuningsih; Mutiara Rengganis (Lembaga Pengembangan Kinerja Dosen, 2023)
This research aims to determine the influence of workload variables, work stress and work motivation on work productivity among PT A B C. This sampling technique uses simple random sampling, with up to 100 respondents. The measurements in this questionnaire use an Ordinal scale. The data analysis technique in this research uses the IBM SPSS v22 software application with the path analysis method (path analysiss). The analysis used in this research includes validity test, reliability test, normality test, coefficient of determination test, t test and Sobel test. The results of this study show that workload has a direct negative and significant effect on work motivation, work stress has a direct negative and significant effect on work motivation, workload has a direct negative and significant effect on work productivity, work stress has a direct negative and significant effect on work productivity, motivation work has a direct positive effect on work productivity, workload has an indirect effect on work productivity through work motivation and work stress has an indirect effect on work productivity through work motivation.